PD-L1 expression is associated with epithelial-mesenchymal transition in head and neck squamous cell carcinoma - Ock, Chan-Young (Impact Journals LLC, 2016)
Virus-associated malignancies and sarcomatoid cancers correlate with high PD-L1 expression, however, underlying mechanisms remain controversial. We evaluated the correlation between PD-L1 expression and epithelial-mesenchymal transition (EMT) in head and neck squamous cell carcinomas (HNSCC). Tumor tissues from 50 patients with HNSCC were evaluated for PD-L1 by immunohistochemistry, which showed 32 (64.0%) were PD-L1 positive (PD-L1+). Interestingly, PD-L1 expression was significantly associated with EMT (P = 0.010), as assessed by low E-cadherin and high vimentin expression. The overall survival of PD-L1+ patients with EMT features was significantly worse than those without EMT features (P = 0.007). In an independent validation cohort (N = 91), as well as in HNSCC cases of The Cancer Genome Atlas (TCGA) and the Cancer Cell Line Encyclopedia, high PD-L1 expression was also associated with the high probability of an EMT signature, referred from the GEO dataset, GSE4824. Survival analysis confirmed PD-L1+/EMT+ patients had a poorer prognosis than PD-L1+/EMT- patients in the TCGA cohort. PD-L1 positivity can thus be divided into two categories according to the absence or presence of EMT. PD-L1 expression is also independently associated with EMT features in HNSCC.